2006
DOI: 10.1016/s0022-5347(05)00140-0
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Volume Alters Cholinergic Responses of the Isolated Whole Mouse Bladder

Abstract: The response to cholinergic stimulation of the isolated bladder has 3 components. The initial tonic peak response increases with bladder distention and it is inhibited by M2 and M3 muscarinic receptor antagonists. The tonic steady state response does not vary with bladder volume and it is inhibited by M2 and M3-receptor antagonists, and by beta3-adrenergic receptor agonists. Phasic fluctuations are minimal at low bladder volume, and with alpha, beta-methylene adenosine triphosphate or an M3-receptor antagonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 20 publications
3
15
0
Order By: Relevance
“…3A). Both VIP -/-(7.3 ± 2.5 cm H 2 0) and WT (6.3 ± 2.5 cm H 2 0) mice exhibited non-voiding contractions in the absence of bladder inflammation consistent with previous studies ( Lagou et al, 2006;Streng et al, 2006) (Fig. 2Aa, Ab, Ba, Bb).…”
Section: Bladder Function In Wt and Vip -/-Mice Without Bladder Inflasupporting
confidence: 88%
See 1 more Smart Citation
“…3A). Both VIP -/-(7.3 ± 2.5 cm H 2 0) and WT (6.3 ± 2.5 cm H 2 0) mice exhibited non-voiding contractions in the absence of bladder inflammation consistent with previous studies ( Lagou et al, 2006;Streng et al, 2006) (Fig. 2Aa, Ab, Ba, Bb).…”
Section: Bladder Function In Wt and Vip -/-Mice Without Bladder Inflasupporting
confidence: 88%
“…Both WT and VIP -/-mice demonstrated evidence of phasic, non-voiding contractions during intravesical saline infusion. The functional significance and origin (myogenic vs. neurogenic) of these non-micturition contractions is not known (Herrera et al, 2003;Lagou et al, 2006;Streng et al, 2006). It has been suggested that non-voiding contractions are associated with mechanoreceptor activation in the detrusor and may contribute to sensations related to bladder volume (Streng et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The doses of pirenzepine (0.3 M) and 4-DAMP (10 nM) tested were determined from the study of Giglio et al (2001) on guinea pig urinary bladder strips. The dose for AF-DX116 (1 M) was based on the work of Lagou et al (2006). In the present study, exogenous application of carbachol elicited a robust contractile response of 29.7 Ϯ 2.8 cm H 2 O.…”
Section: Resultsmentioning
confidence: 68%
“…On the basis of these observations, subsequent studies were carried out over the volume range 0.12 to 0.15 ml. These test volumes have been further validated by a recent publication of Lagou et al (2006), in which they found in a similar model that the peak contraction occurred at a volume range of between 0.1 and 0.12 ml. EFS parameters sensitive to TTX were determined as indicated in Fig To establish whether the dual nature of neurotransmission seen in other mammalian bladders also applied to the mouse, the sequential effects of atropine and atropine plus ␣,␤,methyleneATP on the frequency response curves were determined, and the results compared with similar experiments on isolated muscle strips, as shown in Fig.…”
Section: Resultsmentioning
confidence: 85%
“…In addition to efferent input, local reflexes may contribute to the inhibition of detrusor activity, probably driven by interstitial cells,114 so that peripheral autonomous activity increases as a result of bladder distension 115,116. This has been proposed to signify the presence of a regional regulatory influence117 and a peripheral “pacemaker”118 and various mechanisms for the propagation of activity within the bladder wall 119.…”
Section: Efferent Pathways To the Bladdermentioning
confidence: 99%